Folic acid modified Pluronic F127 coating Ag2S quantum dot for photoacoustic imaging of tumor cell-targeting. (5th January 2018) - Zhang, Ruo-Yun; Wang, Zhao-Yang; Yang, Xiao-Quan; Xuan, Yang; Cheng, Kai; Li, Cheng; Song, Xian-Lin; An, Jie; Hou, Xiao-Lin; Zhao, Yuan-Di
Abstract: In this study, an oil-soluble Ag2 S quantum dot (QD) was synthesized through thermal decomposition using the single-source precursor method, and Pluronic F127 (PF127), a triblock copolymer functionalized with folic acid (FA), was deposited on the surface of the QD, then a water-soluble PF127-FA@Ag2 S nanoprobe with targeting ability was fabricated. The as-prepared PF127-FA@Ag2 S exhibited spheroidal morphology and high dispersibility, with average diameters of 115 ± 20.7 nm (as observed by transmission electron microscopy). No obvious toxicity of the PF127-FA@Ag2 S nanoprobe was found in standard 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay and colony-formation assay, indicating good biocompatibility and safety. The resulting PF127-FA@Ag2 S exhibited excellent stability between 4 °C–40 °C. Additionally, the capacity of the tumor cell-targeting high contrast enhanced photoacoustic imaging of PF127-FA@Ag2 S was verified in comparison with A547 and HeLa cells. In other words, the excellent properties of PF127-FA@Ag2 S show great potential in further research for targeting and photoacoustic imaging.